2016
DOI: 10.1053/j.semperi.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in the design and analyses of neonatal research studies: Experience of the NICHD Neonatal Research Network

Abstract: Objective Impressive advances in neonatology have occurred over the 30 years of life of The Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network (NRN). However, substantial room for improvement remains in investigating and further developing the evidence base for improving outcomes among the extremely premature. We discuss some of the specific methodological challenges in the statistical design and analysis of randomized trials and observational studies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…An important issue in designing studies involving high-risk patients is the selection of an appropriate primary outcome when death is a competing outcome32. In this situation, some patients will die before the outcome of interest can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue in designing studies involving high-risk patients is the selection of an appropriate primary outcome when death is a competing outcome32. In this situation, some patients will die before the outcome of interest can occur.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, some patients will die before the outcome of interest can occur. For this reason, a composite outcome including death is often used when complications of prematurity such as BPD or NEC are studied32. Since the onset of ‘classical’ NEC takes place around the end of the third week of life3334, we performed an additional analysis in which the infants with NEC were combined with the infants who died before 34 weeks of corrected GA. Interestingly, we observed that the minor A-allele was significantly less frequent among the infants with the combined outcome NEC or death.…”
Section: Discussionmentioning
confidence: 99%
“…We included major morbidities used in neonatal outcomes research for their known association with quality of care and long-term neurodevelopment of preterm infants3 28: bronchopulmonary dysplasia (need for supplemental oxygen at 36 weeks’ postmenstrual age or at time of discharge if prior),29 severe neurological injury (grade ≥3 intraventricular haemorrhage according to Papile et al 30 and/or periventricular leukomalacia based on ultrasound findings), severe retinopathy of prematurity (stage ≥3 in at least one eye based on international classification31 or treatment with laser or ophthalmological injection), necrotising enterocolitis (stage ≥2 according to Bell’s criteria)32 and nosocomial infection (positive blood or cerebrospinal fluid culture in a symptomatic neonate after at least 3 days in the NICU). A composite outcome was selected because mortality (which typically occurs in first 2 weeks of life) and morbidities (which typically occur later (but are related to early interventions) are competing events in very preterm infants 33…”
Section: Methodsmentioning
confidence: 99%
“…Because of the inability of randomization, ethical considerations, lack of resources, or lack of equipoise, most epidemiological studies conducted in perinatal research are observational. 26 The concern with observational (non-experimental) studies is bias, which might arise from flaws in the study design, recruitment, conduct of the study, or in the presentation of the results. 1 In fact, this issue was recently explored in umbrella reviews that evaluated the credibility of evidence of previously published systematic reviews and meta-analyses of observational studies in crucial pregnancy complications, such as preeclampsia and gestational diabetes, and predictors for subsequent disease such as birth weight.…”
Section: Bias and Confounding In Observational Studiesmentioning
confidence: 99%
“…42 In addition, group sequential designs can be helpful to reduce sample size by stopping studies early if effect sizes differ from what is expected. 26,43 Adaptive and internal pilot designs are also promising as they can use interim power analyses to adjust the sample size for misspecification of parameters, while the second allows early stopping for efficacy and futility. 43,44 Recruitment challenges in perinatal research could be overcome by enhancing the visibility of research in social media, increasing sampling frame, ensuring that the research team provides adequate information and support, and explicitly address fetal issues to strengthen women’s self-efficacy, as well as networking with clinicians at recruitment sites.…”
Section: Recommendationsmentioning
confidence: 99%